2013
DOI: 10.1093/arclin/act001
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Fluency and Phonemic Fluency: Regression-based Norms for the Portuguese Population

Abstract: The main goal of this study was to produce adjusted normative data for the Portuguese population on two verbal fluency measures: the semantic fluency test (animals category) and the phonemic fluency test (letters M, R, and P). The study included 950 community-dwelling individuals (624 women and 326 men) aged between 18 and 98 (mean = 57.8, SD = 19.0), who had educational backgrounds ranging from 0 to 20 years (mean = 8.8, SD = 5.2). The results showed that age and education were significantly associated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
69
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 63 publications
10
69
1
11
Order By: Relevance
“…The present study revealed that, with the exception of alternating fluency, all categories were affected by age (a progressive age-related decrease in the number of generated words), as in previous studies [12,13,18,19,20,21,22,23,24,35,36]. Alternating fluency had a negative correlation with age as in other studies [11,27].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The present study revealed that, with the exception of alternating fluency, all categories were affected by age (a progressive age-related decrease in the number of generated words), as in previous studies [12,13,18,19,20,21,22,23,24,35,36]. Alternating fluency had a negative correlation with age as in other studies [11,27].…”
Section: Discussionsupporting
confidence: 88%
“…In a healthy population such as the one in the present study, the effect of age probably disappears in the presence of years of education. Moreover, education affects all categories, a finding similar to what was found by other authors [12,13,18,19,20,21,22,23,37,38,39]. Essentially, when an effect of education is found, the assumption is that education increases the individual's exposure to vocabulary.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations